The Effect of CEO Narcissism, Company Size, and Free Cash Flow on Financial Performance through CSR in SOEs on the IDX 2018-2022 - Gunawan Hadi Prastiyono; Andini Nurwulandari (Jurnal Indonesia Sosial Teknologi, 2024)
This study aimed to determine the effect of CEO Narcissism, Company Size, and Free Cash Flow through Corporate Social Responsibility (CSR) on Financial Performance in State-owned enterprises Companies. This study uses a quantitative approach with data sources from the Indonesia Stock Exchange (IDX) official website using the Warppls 7.0 application. The research sample data were from 16 state-owned enterprise companies. The test results show that CEO Narcissism has a negative and significant effect on Corporate Social Responsibility (CSR), Company Size has a negative and insignificant effect on Corporate Social Responsibility (CSR), Free Cash Flow has a positive and insignificant effect on Corporate Social Responsibility (CSR), CEO Narcissism is unable to mediate the effect of Corporate Social Responsibility (CSR) on financial performance. Company Size cannot mediate the effect of Corporate Social Responsibility (CSR) on financial performance. Free Cash Flow cannot mediate the influence of Corporate Social Responsibility (CSR) on financial performance. The Total Determination Coefficient in this study is 0.285 or 28.5%. This indicates the model can explain 28.5% of the data's information. Other factors not included in the study model account for the remainder.